Shipping law - Baughen, Simon (London : Routledge-Cavendish, 2009)
Covering English shipping law, this book takes into account developments such as the 2007 Wreck Removal Convention and the Rotterdam Rules on contracts for the international carriage of goods wholly or partly by sea. It provides analysis of various judicial decisions, such as that of the European Court of Justice in Owusu v Jackson
1. The commercial background -- 2. Title to sue -- 3. Providing loss or damage in transit -- 4. The terms of the bill of lading contract -- 5. Statutory terms of the bill of lading contract -- 6. The future : the Hamburg Rules and the Rotterdam Rules -- 7. Combined transport -- 8. Carriage by road-CMR -- 9. Charterparties -- 10. Voyage charterparties-payment of freight -- 11. Voyage charters-laytime and demurrage -- 12. Time charters -- 13. Damages and frustration -- 14. Collisions -- 15. Salvage -- 16. General average -- 17. Marine pollution -- 18. Jurisdiction and applicable law -- 19. Security and interim relief -- 20. Limitation of liability
Includes bibliographical references and index
Keywords: Maritime law -- Great Britain